2019
DOI: 10.1108/jes-08-2017-0243
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of sector growth and monetary policy on income inequality in developing countries

Abstract: PurposeThe purpose of this paper is to explore the effect of growth in different sectors of the economy of developing countries on income inequality and analyze how inflation, as a proxy for monetary policy, makes a proportionate contribution for setting a binding national target for reducing income inequality. The paper examines the existence of a linear or nonlinear effect of inflation and sectoral economic growth on income inequality using a balanced panel data of 92 developing countries for the period of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In all models, the coefficients of the CPI inflation are positively significant. It means that a rise in the CPI inflation, as an indirect effect of monetary policy shocks, can increase income inequality, which is consistent with the results of previous studies (Shiller, 1996; Easterly & Fischer, 2001; Amornthum, 2004; Siami‐Namini, 2019; Siami‐Namini & Hudson, 2019a,b). No matter what measures are used as an income inequality indicator in the estimated models, the effects of CPI inflation on income inequality are similar for all individual measures.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In all models, the coefficients of the CPI inflation are positively significant. It means that a rise in the CPI inflation, as an indirect effect of monetary policy shocks, can increase income inequality, which is consistent with the results of previous studies (Shiller, 1996; Easterly & Fischer, 2001; Amornthum, 2004; Siami‐Namini, 2019; Siami‐Namini & Hudson, 2019a,b). No matter what measures are used as an income inequality indicator in the estimated models, the effects of CPI inflation on income inequality are similar for all individual measures.…”
Section: Resultssupporting
confidence: 91%
“…The results indicated that there is no bi‐directional Granger causality between inflation and income inequality in the short run, but there is, in the long run, for both groups. In another study, Siami‐Namini and Hudson (2019b) analysed the impacts of sectors’ growth and monetary policy on income inequality in a balanced time series panel data of developing countries for the period of 1990–2014. They found that agricultural and industrial sectors’ growth has a dominant impact in reducing income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Siami-Namini and Hudson (2019) examined the impacts of sector growth and monetary policy on income inequality by using a cross-country panel of 92 developing countries for the period of 1990–2014. They found that agricultural and industrial growth have a negative effect, while service sector growth has a positive effect on income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The agricultural sector has a vital role in national development, including as a source of foreign exchange for the country, contributing GDP, employment, industrial raw materials, sources of food and nutrition, as well as encouraging the movement of other real economic sectors (Devaux, Torero, Donovan, & Horton, 2018;Siami-Namini & Hudson, 2019). Along with its development, companies engaged in the agricultural industry will expand their business by entering into international markets (Amanor & Chichava, 2016;Graeub et al, 2016;Liu, Hertel, Taheripour, Zhu, & Ringler, 2014).…”
Section: Introductionmentioning
confidence: 99%